The ESCAPER study—exploring protective mechanisms against cardiovascular disease in subjects at high risk: rationale, study protocol, and first results - Ekström, Ola; Arheden, Håkan; Christensson, Anders; Engström, Gunnar; Hedström, Erik; Kennbäck, Cecilia; Laucyte-Cibulskiene, Agne; Lundgren, Simon; Lyssenko, Valeriya; Löndahl, Magnus; Magnusson, Martin; Nilsson, Peter M.; et al. (Scandinavian cardiovascular journal : SCJ, 2025)
The ESCAPER project explores cardiovascular resilience in individuals who, despite a high-risk factor burden-longstanding Type 1 Diabetes (T1D), obesity, or kidney failure-avoid or delay macrovascular complications. This suggests underlying protective mechanisms. Initiated in September 2022, this exploratory study aims to uncover and define these mechanisms, potentially leading to novel therapeutic targets in preventive medicine. Participants from the Skåne region, Southern Sweden, are divided into three subgroups: (1) T1D patients (>30 years duration) without macrovascular complications or macroalbuminuria, (2) obese individuals with normal cardiac function and no cardiovascular medications, and (3) kidney failure patients awaiting transplantation with no arterial calcification, alongside respective controls. Comprehensive phenotyping includes 24-h blood pressure, ECG monitoring, vascular ultrasound, cardiac MRI, and ergospirometry (in a subgroup), along with laboratory investigations, including biomarker and omics analyses. Arterial biopsies are collected from kidney failure patients. The study leverages Swedish national medical registries for detailed follow-up of healthcare utilization, diagnoses, and prescriptions, enabling longitudinal outcome assessments. Initial findings from 90 T1D patients and 31 obese individuals indicate well-managed cardiovascular risk factors. The T1D subgroup shows a mean BMI of 25.6 kg/m and HbA1c of 52 mmol/mol, while the obesity subgroup presents a BMI of 32.9 kg/m with normal glucose levels. ESCAPER has the potential to advance understanding of cardiovascular resilience and refine prevention strategies. Its comprehensive methodology and registry-based follow-up provide robust insights into protective mechanisms and long-term outcomes.